Analisis Keragaman Genetik Tikus Hutan Ekor Putih (Maxomys hellwandii) Berbasis RAPD - Mege, Revelson A.; Rompas, Christny Ferdina; Wulandari, Wulandari (Universitas Negeri Manado, 2020)
White-tailed forest mice (Maxomys hellwandii) are endemic to the Sulawesi. This study aims to determine the genetic diversity of white-tailed forest mice (Maxomys hellwandii) based on RAPD. The analysis of the variability of white-tailed forest rats was carried out in several stages, namely the extraction and purification of DNA, the amplification of the target gene using the PCR method, and finally visualization of the amplification results with 0.8% agarose gel electrophoresis. Data analysis using the SPSS IBM Ver. 20 program. Results obtained using OPA-3 primers from four different localization samples show samples of Likupang 1 and South Minahasa show similarity of 1%, and samples of Likupang 2 and Southeast Minahasa show similarity of 25%. Whereas the primary OPA-2 samples from the villages of Likupang 1, Likupang 2 and South Minahasa show a similarity of 8% and the sample of Southina Minahasa has a similarity of 25%. On the basis of the dendogram grouping of four different samples, he showed genetic diversity.